第55次日本南極地域観測隊東京海洋大学練習船「海鷹丸」(KARE-17；UM-13-09）活動報告 - 茂木, 正人; モテキ, マサト; Moteki, Masato (国立極地研究所, 2016)
2013/2014 年南半球夏シーズンに，東京海洋大学練習船「海鷹丸」の海洋研究航海（KARE-17; UM-13-09）が，南大洋インド洋区で行われた．この航海では，東京海洋大学・国立極地研究所の連携事業として，文部科学省委託事業「南極地域観測事業基本観測」を実施したほか，両機関の共同研究として，日本南極地域観測第Ⅷ期計画の研究課題である「プランクトン群集組成の変動と環境変動との関係に関する研究」，「海洋生態系モニタリング」及び東京海洋大学・極地研究所共同研究「南大洋の環境変動と生態系変動」が実施された．更に，重点研究観測サブテーマ2「南極海生態系の応答を通して探る地球環境変動」，東京海洋大学・独立行政法人海洋研究開発機構（JAMSTEC）共同研究「海鷹丸における深海観測用フロート投入」も実施された．海鷹丸は平成26年1月11日，フリーマントルを出港後，東経110度の海氷縁に及ぶ海域の観測を行い，平成26年2月5日，ホバート港へ寄港した．この間，海洋物理・化学観測では，海氷縁海域において海底直上までのCTD（Conductivity Temperature Depth profiler）観測が行われ，南極底層水の性質を高い精度で観測することができた．また，第Ⅷ期計画課題に関連して，プランクトン群集の定量的な鉛直分布を調べるため各種ネットによる観測や，「しらせ」が放流した漂流ブイの回収，生態系や南極底層水の動態を調べる長期係留系の回収・設置が行われた． A marine science cruise was undertaken in the Indian sector of the Southern Ocean during the 2012/2013 austral summer on the training vessel Umitaka-maru (KARE-17; UM-13-09) of the Tokyo University of Marine Science and Technology (TUMSAT). ＂Japanese Antarctic Research Expedition (JARE) Routine Observation: Physical and Chemical Oceanography＂, commissioned by the Ministry of Education, Culture, Sports, Science and Technology, was conducted as a TUMSAT and National Institute of Polar Research (NIPR) collaborative project. The TUMSAT-NIPR collaborative programs, ＂Studies on Plankton Community Structure and Environment Parameters in the Southern Ocean＂ and ＂Marine Ecosystem Monitoring＂ (the JARE phase VIII projects), and ＂Environment and Ecosystem Changes in the Southern Ocean＂ were conducted. In addition to these TUMSAT-NIPR collaborative programs, the other phase VIII project, ＂ Responses of Antarctic Marine Ecosystems to Global Environmental Changes with Carbonate Systems＂, and the TUMSAT and Japan Agency for Marine-Earth Science and Technology (JAMSTEC) collaborative program ＂Deployment of Deep Ninja＂ was conducted. The Umitaka-maru departed from Fremantle, Australia, on 11 January 2014, sailed to the study area around the marginal sea ice zone along 110°E, and returned to Hobart, Australia, on 5 February 2014. Physical and chemical Oceanographic observations, using a CTD (Conductivity ...